Consider the octopus - Baskin, Nora Raleigh; Polisner, Gae (Godwin Books : Henry Holt and Company, 2022)
JB Barnes' summer plan of hanging out on the beach is suddenly cancelled when his mother, a research scientist, takes him along on her ship to study the Great Pacific Garbage Patch and all the damage it is causing to marine species. Meanwhile, worlds away, Sidney Miller wants a way to get out of her overprotective parents' summer camp plans for her--that chance comes when JB, doing email invitations to an Emergency Global Summit for his mother, sends an invite to Sidney, who shares a name with a prominent international scientist. Sidney, shocked at her luck, agrees and boards ship with JB, where the two kids embark on a cruise and comedy of errors where they might just become friends and help save the ocean.